Sketching 25 April: The Carnation Revolution - Ramos, M. (Mixed Methods Workshop - Project FamilEA in collaboration with Project AfDevLives, 2024)
"Sketching 25 April: The Carnation Revolution" is a walk-workshop that combines ethnographic observation and sketching to engage with the living memory of Portugal’s 25 April Revolution. By walking through historically significant sites, participants immerse themselves in the urban landscape, documenting their surroundings through drawing as a form of visual ethnography. This practice enhances observational skills, fosters embodied learning, and captures the interplay between history, space, and collective memory. Sketching serves not only as a methodological tool but also as a reflective act, allowing for a deeper engagement with the social and political narratives embedded in Lisbon’s streets. Through this approach, the workshop highlights how visual documentation can complement anthropological inquiry, offering new perspectives on cultural heritage and public history.